2D-QSAR, Docking, Molecular dynamics simulations with the MM/GBSA approaches against Grave's disease and PTPN22 - Emmanuel Israel Edache; Adamu Uzairu; Paul Andrew Mamza; Gideon Adamu Shallangwa (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Graves' disease (GD) is an autoimmune condition that frequently causes hyperthyroidism and thyrotoxicosis. Protein tyrosine phosphatase, non-receptor type 22 (lymphoid) isoform 1 (PTPN22), is a promising therapeutic candidate for treating Graves' disease, rheumatoid arthritis, type 1 diabetes, and other autoimmune disorders. In this dataset, 31 molecular compounds and two standard drugs were optimized using the semi-empirical PM7 theory method via MOPAC v22.0.4 to reveal the key influencing factors contributing to their grave's disease inhibition activity and selectivity. Using QSARIN software, the acquired properties/descriptors were used to create a quantitative structural activities relationship (QSAR) model, and the similarities between the observed and predicted pIC50 values were examined. A molecular docking simulation study also uncovers non-covalent interactions between the investigated compounds and the receptors. The observed ligand-protein interactions with grave's disease proteins (PDB ID: 2XPG and 4QT5) and protein tyrosine phosphatase, non-receptor type 22 (lymphoid) isoform 1 (PTPN22) (PDB ID: 3BRH) were investigated. The pharmacokinetics (ADMET) properties were also investigated. Finally, molecular dynamics (MD) simulation and MMGBSA studies that demonstrated stable trajectory and molecular properties with a consistent interaction profile were used to validate the stability of the compounds in the complex with PTPN22.